Teologi di Era Post-Truth dan Tantangan Gereja dalam Menyampaikan Kebenaran di Tengah Hoaks dan Disinformasi - Leki Tamukun, Adam Yordan; Labatar, Daniel; Bria, Zhakarias; Firman, Karifansius (Jurnal Masalah Pastoral, 2025)
The purpose of this study is to analyze the role of the church in addressing the challenges of the post-truth era in conveying truth amid the spread of hoaxes and disinformation. This study employs a qualitative approach using literature analysis and case studies on information dissemination in church digital media. Primary data sources include theological studies, previous research, and analysis of church digital media content. The findings indicate that hoaxes and disinformation in religious contexts weaken church authority, polarize congregations, and lead to theological misunderstandings that deviate from church doctrine. The church needs to develop effective strategies to combat disinformation, such as enhancing digital literacy among congregants, strengthening pastoral theology, and optimizing social media as a platform for spreading the true teachings. This study emphasizes that the church’s role in safeguarding truth must be proactive to prevent congregants from falling into misleading information. By adopting an approach based on God’s word and effective communication aligned with technological advancements, the church can continue to be a guardian of truth in the post-truth era.